513Ophthalmic disease and older adults' sedentary and physically-active behaviors: Findings from the NEIGE study. (2nd September 2021) - Amagasa, Shiho; Inoue, Shigeru; Murayama, Hiroshi; Fujiwara, Takeo; Kikuchi, Hiroyuki; Fukushima, Noritoshi; Machida, Masaki; Chastin, Sebastien; Owen, Neville; Shobugawa, Yugo
Abstract: Background: Physical inactivity can be associated adversely with markers of eye health, but little is known about how ophthalmic disease (OD) may be related to sedentary behaviour (SB) and different intensities of physical activity in older adults. We compared device-assessed time spent in SB, light-intensity PA (LPA), and moderate-to-vigorous physical activity (MVPA) between older adults with and without OD. Methods: A randomly-recruited sample of 512 community-dwelling older adults (47% male; aged 65–84 years) in Japan wore a valid tri-axial accelerometer for seven consecutive days in 2017. Prevalence of OD was assessed by medical interview. Times spent in SB, LPA, and MVPA were compared between those with and without OD by compositional multivariate analysis of covariance, adjusting for potential confounders (gender, age, residential area, living arrangement, working, body mass index, self-rated health, and cognitive function). Results: Overall, percent times spent in SB, LPA, and MVPA during waking hours were 51.0, 44.6, and 4.4, respectively; and, 167 (36.5%) had OD. Activity patterns differed significantly between those with and without OD: in those with OD, the proportion of time spent in MVPA relative to other behaviours was lower, and the proportion of time spent in SB relative to other behaviours was higher. Conclusions: Older adults with OD were found to be less physically active than those without. Key messages: While these cross-sectional findings need to be confirmed by evidence from prospective studies, the reciprocal influences of OD and inactivity in older adults should be addressed as scientific, clinical and public health considerations.